Sosialisasi Strategi Peningkatan Kualitas Pendidikan Melalui Metode Pembelajaran Kreatif dan Inovatif di Desa Rantau Bintang - Muhammad Zulkar Syahfitra; Yuria Nadila; Fatia Sari; Ahmad Zaki; Hayatun Sabariah (Fusion: Jurnal Pengabdian kepada Masyarakat, 2024)
Education is the most important thing nowadays, with education humans can become quality human beings and be able to live a good life. To make this happen, as a teacher/educator you must strive for student success in learning. Method of implementing KKN service by STAI Jam'iyah Mahmudiyah Tanjung Pura students in Rantau Bintang Village KEC.Bandar Pusaka KAB.Aceh Tamiang regarding "Socialization of strategies for improving the quality of education through creative and innovative learning methods". It is hoped that this research can change learning strategies that are not only able to work but can be digested and are enjoyable for students.Through an inclusive and participatory approach, the KKN team from STAI Jam'iyah Mahmudiyah Tanjung Pura is able to design and implement programs that do not only focus on aspects Education, but also the learning process.